The implementation of online learning in teaching english for athlete students - Khusnul Khatimah; Rani Herning Puspita; Dzul Rachman; Waladdin Panggabean (Linguista: Jurnal Ilmiah Bahasa, Sastra, dan Pembelajarannya, 2021)
The development of information technology that can be used as a learning medium is ICT (information and communication technologies). This learning model is an innovation that can be implemented in the learning process, not only in the delivery of learning material but also changes in the abilities of various competencies of students. In fact, some universities have athlete student who cannot attend in class because of his activities such as championship or matches. Based on the situation, the researcher should have a solution, so that the athlete students still can follow the lesson Based on the problem formulation that has been described, the research objectives to be achieved are 1). Increase motivation to learn English athletes at Muhammadiyah University of East Kalimantan through online learning; 2). Improving the results of learning English athletes of Muhammadiyah University students in East Kalimantan through Online learning. With learning using online learning students can facilitate them in accessing their courses, completing assignments without having to be present in class. Learning using open learning has been proven to increase the ability to understand basic English in athlete students